Will Curiosity® Kill the Cat? Technoscience and Free Living Cats “Down Under” - Bunyak, Garrett (Humanimalia, 2019)
The control and eradication of free-living domestic cats due to perceived declines in bird populations is a major concern within the biological and ecological sciences, especially in Australasia. Consequently, human relationships with free living cats are entangled with deadly technoscientific discourses and practices. Deploying a posthumanist framework, this genealogy examines efforts to manage and destroy free-living cat populations with and through technoscience. Scientific recourse to constructs such as rationality and progress, grounded in Enlightenment philosophy, are shown to legitimize and enable scientific efforts to control and master “nature” and free-living cats. The consequences for non-human animals and indigenous peoples are discussed. Extending interdisciplinary work in science studies, the paper suggests the scientific accounts analyzed are haunted by legacies of colonialism, human exceptionalism, and a faith in science, technology, and progress. As a microcosm of broader trends, this case suggests a scientific enterprise geared towards controlling the “non-human world” may be more of a threat to global ecological processes than the very problems scientists are attempting to solve.